A high performance scintillator-silicon-well x-ray microdetector based on DRIE techniques - Rocha, J. G. (2001)
This paper proposes a X-rays detector based on an array of scintillator crystals, CsI:Tl, encapsulated in a well that is etched into a silicon substrate by deep reactive ion etching. The X-ray energy is first converted to visible light which is detected by a photodetector in the well bottom. DRIE techniques are used to achieve perfect vertical side-walls 515um deep, 100um pixel square size and to maximize the fill factor. The inner walls of the well that are coated with aluminum for improving the number of photons which arrives to the detector and for reducing cross-talk between adjacent wells. Simulations and modeling show an improvement of approximately 26% in the detection efficiency using an aluminum layer.